MAIN ASPECTS OF ORGANIZING INNOVATIVE TEXTILE CORPORATIONS FROM UZBEKISTAN (Academicia Globe: Inderscience Research, 2024)
This article presents specific aspects of the organization of innovative textile corporations. The main tasks of organizing the essence of the textile industry, the main tasks of organizing production in the textile industry and the properties of innovative companies are analyzed. Moreover, approaches to the concept of an innovative company have been researched. Types of innovative companies, venture companies, exploitative companies, violent companies, and stages of development of innovative companies were studied, and practical recommendations were given on the main aspects of the organization of innovative textile corporations.